The Role of Leader Boundary Activities in Enhancing Interdisciplinary Team Effectiveness. (February 2015) - Benoliel, Pascale; Somech, Anit
This study examined how leaders' internal and external activities mediate the relationship of functional heterogeneity and interteam goal interdependence to team effectiveness (in-role performance and innovation) in interdisciplinary teams. The results of the structural equation model from a sample of 92 interdisciplinary teams indicate that leaders' internal activities fully mediate the relationship of team functional heterogeneity and interteam goal interdependence to team in-role performance. The leaders' external activities were found to fully mediate the relationship of interteam goal interdependence to team innovation. We discuss the implications of these findings for both theory and practice.